Conclusion: externalism, internalism, and idealism - Rowlands, Mark (Externalism, 2003)
Chapter 1 characterized the concept of Cartesian internalism in terms of two claims, one concerning the location of mental phenomena and the other concerning the possession of such phenomena by a subject. Cartesian internalism The Location Claim: any mental phenomenon is spatially located inside the boundaries of the subject, S, that has or undergoes it. The Possession Claim: the possession of any mental phenomenon by a subject S does not depend on any feature that is external to the boundaries of S.